EL LÉXICO DISPONIBLE DE VALENCIA: CONVERGENCIA CONCEPTUAL - M.ª Begoña Gómez Devís; Francesc Llopis Rodrigo (Revista de Lingüística y Lenguas Aplicadas)
The present research pretends to show the degree of semantic merging between the available lexis of Spanish and Catalan from Valencia in 2nd year baccalaureate students. The global inter-linguistic compatibility for speakers of both linguistic communities in the seventeen semantic groups studied will show the high level of coincidence in both languages in contact. This is due to the fact that the lexis used in specifi c communicative situations is similar in both. El presente trabajo pretende mostrar el grado de convergencia semántica entre el léxico disponible del español y del catalán de Valencia en los estudiantes de segundo de bachillerato. La compatibilidad global interlingüística de los hablantes de ambas comunidades lingüísticas en los diecisiete campos semánticos mostrará un alto nivel de coincidencia en las dos lenguas en contacto. Esto se debe a que el léxico usado en situaciones comunicativas concretas es similar en las diferentes lenguas de cultura.